Physicochemical, microbial, and aflatoxin analyses of selected high-quality cassava flour (HQCF) from the major markets of Zambia - Alamu, Emmanuel Oladeji; Gondwe, T.; Ayinde, O.; Akinwale, M.G.; Ntawuruhunga, P.; Awoyale, W.; Abass, A.; Maziya-Dixon, Busie (Informa UK Limited, 2021)
Various quality grades of high-quality cassava flour (HQCF) are found in markets due to the rapid increase in its utilization for product development. Therefore, this study assessed the chemical, functional and pasting properties and the microbial and aflatoxin content of HQCF being sold in Lusaka markets. Nine samples of HQCF (coded CM 01 to 09) were collected from supermarkets, one major open market, and one cassava processing centre. The samples were analyzed for chemical, functional and pasting properties and the microbial and aflatoxin content using standard laboratory methods. Samples CM 01, CM 08, and CM 09 had starch content above 60%, while CM 02 to CM 07 had starch slightly above 40%. The mean value of bulk density (BD) was 0.51 ± 25.49 g ml−1, dispersibility 68 ± 2.63%, swelling power (SP) 7.84 ± 0.76%, solubility index 135.80 ± 18.8%, and water absorption capacity (WAC) 6.28 ± 32.49%. The mean value for the peak viscosity was 437.46 ± 94.12 RVU, trough viscosity 217.55 ± 27.41 RVU, breakdown viscosity 219.91 ± 77.94 RVU, final viscosity 284.31 ± 29.96 RVU, and setback viscosity 66.77 ± 5.30 RVU. There was no detection of aflatoxins B1, B2, G1, and G2, especially aflatoxin B1 (AFB1) that belongs to group 1 carcinogens for humans. Bacteria colony counts in samples CM 02, CM 03, CM 07, and CM 09 were higher with CFU mg−1 of 2,280,000, 260,000, 200,000, and 510,000, respectively. The study’s information will guide the quality standard specifications, breeding programs, and end-use of HQCF.